Identification and degree of parasitism for ticks in canine of San Luis area - Amarilis - Huánuco 2011 - Tasayco Alcántara, Richard (2017)
The present work was carried out in the five sectors of the AA.HH San Luis of the district of Amarilis - Huánuco, located in the area west of the district in mention. The objective was to identify the species of ticks and the illness degree in canine in relation to the race, sex, age and feeding type. The tick identified in the present area (AA.HH San Luis) it was only, being the identified species the Rhipicephalus sanguineus (100% of the dogs with ticks N = 214). as for the illness degree, one has that 56.32% of the animals is infested, in front of 43.68% that don't possess ticks. The sector of the AA.HH with more garrapatosis incidence is the sector four with 17.1%. Mostly the animals that live in the house / he/she remains silent  (65.1%) they are those that present illness for ticks, contrary to those that live alone in its house. The age of the animal more affected by ticks they are the adults (70.1%). in relation to the sex, it was that the males are those most affected ones (63%), and as for the race of the animal, the crossing animals or Creoles are those most affected ones (77%), all this due that is an area with faulty socioeconomic and cultural level. Besides that the illnesses for ticks in most is light (83.6%).